2008
DOI: 10.2527/jas.2008-0882
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effect of animal maturity on muscle characteristics in different muscles, breeds, and sexes of cattle

Abstract: The effect of animal maturity on fiber cross-sectional area, percentage of fiber types, activities of isocitrate dehydrogenase (ICDH) and lactate dehydrogenase (LDH), total and insoluble collagen and lipid concentration was investigated in the longis-simus thoracis (LT), semitendinosus (ST), and triceps brachii (TB) muscles. The analysis considered 2,642 muscle samples from bulls, steers, and cows of Aubrac, Charolais, Limousin, Montbéliard, and Salers breeds. For the bulls, the fiber cross-sectional area, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 27 publications
(48 reference statements)
7
45
1
4
Order By: Relevance
“…The young bulls were slaughtered at 17 months of age on average and the steers at 30 months of age on average at the INRA experimental slaughterhouse in compliance with current ethical guidelines for animal welfare. Muscle samples from the Longissimus thoracis (LT; fast oxido-glycolytic with 25% of myosins of heavy chains I (MyHC-I), 62% of MyHC-IIa and 13% of MyHC-IIx in our experiment by electrophoresis (Picard et al, 1999), and in accordance with Jurie et al (1995Jurie et al ( , 2007 in bovine) and Semitendinosus (ST; fast glycolytic with 11% of MyHC-I, 24% of MyHC-IIa and 66% of MyHC-IIx in our experiment, and in accordance with Schreurs et al (2008) in bovine) muscles were excised for each animal within 15 min after slaughter. Muscle samples were immediately frozen in liquid nitrogen and stored at 2808C until protein extraction.…”
Section: Animals and Samplessupporting
confidence: 78%
See 1 more Smart Citation
“…The young bulls were slaughtered at 17 months of age on average and the steers at 30 months of age on average at the INRA experimental slaughterhouse in compliance with current ethical guidelines for animal welfare. Muscle samples from the Longissimus thoracis (LT; fast oxido-glycolytic with 25% of myosins of heavy chains I (MyHC-I), 62% of MyHC-IIa and 13% of MyHC-IIx in our experiment by electrophoresis (Picard et al, 1999), and in accordance with Jurie et al (1995Jurie et al ( , 2007 in bovine) and Semitendinosus (ST; fast glycolytic with 11% of MyHC-I, 24% of MyHC-IIa and 66% of MyHC-IIx in our experiment, and in accordance with Schreurs et al (2008) in bovine) muscles were excised for each animal within 15 min after slaughter. Muscle samples were immediately frozen in liquid nitrogen and stored at 2808C until protein extraction.…”
Section: Animals and Samplessupporting
confidence: 78%
“…According to the literature data, the ST muscle may exhibit a lower oxidative activity and a strong higher glycolytic activity notably a higher LDH activity compared to the LT (Jurie et al, 1995). The LT muscle that contains a higher proportion of slow fibres and higher oxidative metabolism than ST in young bulls is also characterised by a smaller fibre cross-sectional areas compared to the ST muscle (Schreurs et al, 2008). In this study, we observed a muscle-type effect for only two of the glycolytic enzymes quantified: PGM and Eno1.…”
Section: Protein Of Energy Metabolismmentioning
confidence: 99%
“…However, our study showed that at the same age and degree of fatness there was no gender effect on collagen content, collagen solubility, MFI and, consequently, on WBSF. Accordingly, several authors did not find any difference between genders in collagen content (Morgan et al, 1993;Monteiro et al, 2005;Schreurs et al, 2008) and solubility (Monteiro et al, 2005;Schreurs et al, 2008) or realized that it disappeared after carcass fat content adjustment (Crouse et al, 1985;Moloney et al, 2001).…”
Section: Texture Characteristicsmentioning
confidence: 98%
“…We used an updated database since 2007 (Schreurs et al, 2008), which was created to compile experiments conducted at the Herbivore Research Unit (INRA) in France and to allow the investigation of the effects of animal factors such as muscle, gender, breed and DOM on muscle characteristics, usually associated with beef quality. Detailed description of the muscle characteristics included in the database can be found in a study by Schreurs et al (2008).…”
Section: Database Collection and Collagen Determinationmentioning
confidence: 99%
“…DOM of the animal is the major determinant of meat texture primarily because of the maturation of the collagen fibres (Bailey and Light, 1989). However, there are complex interactions among these factors (Boccard et al, 1979;Schreurs et al, 2008;Archile-Contreras et al, 2010).…”
Section: Introductionmentioning
confidence: 99%